Investigation on the Effect of Addition of Fe3+ Ion into the Colloidal AgNPs in PVA Solution and Understanding Its Reaction Mechanism - Roto Roto; Marcelina Marcelina; Nurul Hidayat Aprilita; Mudasir Mudasir; Taufik Abdillah Natsir; Bella Mellisani (Universitas Gadjah Mada, 2017)
Analysis of Fe3+ ion present in aqueous solutions is always of interests. Recently, this ion has been analyzed by colorimetric methods using colloid of silver nanoparticles (AgNPs) in capping agents of polymers. The reaction mechanism between AgNPs and Fe3+ is still subject to the further investigation. In this work, 1,10-phenanthroline was used to probe the reaction mechanism between AgNPs and Fe3+ ion in the solution. The colloids of AgNPs were prepared in the polyvinyl alcohol (PVA) solution and reacted with Fe3+. The colloid surface plasmon absorbance decreases linearly along with the increase in Fe3+ concentration. The addition of 1,10-phenanthroline to mixture changes the solution to red, indicating that the reaction produces Fe2+. This suggests that the reduction of the AgNPs absorbance is the result of oxidation of the Ag nanoparticles along with the reduction of Fe3+.